2017
DOI: 10.1177/0163278717727568
|View full text |Cite
|
Sign up to set email alerts
|

New Device for Intrinsic Hand Muscle Strength Measurement: An Alternative to Strain Gauge Handheld Dynamometer

Abstract: An accurate measurement of intrinsic hand muscle strength (IHMS) is required by clinicians for effective clinical decision-making, diagnosis of certain diseases, and evaluation of the outcome of treatment. In practice, the clinicians use Intrins-o-meter and Rotterdam Intrinsic Hand Myometer for IHMS measurement. These are quite bulky, expensive, and possess poor interobserver reliability (37-52%) and sensitivity. The purpose of this study was to develop an alternative lightweight, accurate, cost-effective forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Measuring of muscle strength and power may be needed while seeking answers to processes such as talent selection, observing training effects, making new training plans, and determining physical fitness in sports. 22,23,30 Strength measurements in the field of medicine may be required in cases such as the diagnosis of diseases and injuries related to the neuro-muscular system, determination of treatment methods, and control of rehabilitation processes. [31][32][33][34]39,51 During the treatment and (or) posttreatment rehabilitation [40][41][42] of injured athletes 28 or sedentary individuals with orthopedic [35][36][37][38] and neurological [31][32][33][34] disorders, due to the limitation of movement caused by the functional disorders in the joints, benefits to the skeletal muscular system can be provided by isometric exercises and measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measuring of muscle strength and power may be needed while seeking answers to processes such as talent selection, observing training effects, making new training plans, and determining physical fitness in sports. 22,23,30 Strength measurements in the field of medicine may be required in cases such as the diagnosis of diseases and injuries related to the neuro-muscular system, determination of treatment methods, and control of rehabilitation processes. [31][32][33][34]39,51 During the treatment and (or) posttreatment rehabilitation [40][41][42] of injured athletes 28 or sedentary individuals with orthopedic [35][36][37][38] and neurological [31][32][33][34] disorders, due to the limitation of movement caused by the functional disorders in the joints, benefits to the skeletal muscular system can be provided by isometric exercises and measurements.…”
Section: Discussionmentioning
confidence: 99%
“…26 From this point of view, observing the strength and power changes of athletes may play an important role in the training of elite athletes, in the regulation of competition preparations and training programs, [21][22][23]26,27 stages of return to sport during 28 and after the injury period. 16,29 In addition to strength and power measurement studies in the field of sports, 22,23,30 patients with neurological/neuromuscular [31][32][33][34] and orthopedic disorders, [35][36][37][38] physical therapy and rehabilitation patients, [39][40][41][42] the elderly, 8,43,44 children, [45][46][47] and various special groups [48][49][50] may also need to be observed the changes in strength and power. Strength and power measurements are used in all these groups, for development purposes, control purposes, 35,36,51 diagnosing diseases, 17,30,52 or planning treatments or creating normative data 17,20,47 by receiving feedback, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…91 In another study, it was shown how a natural rubber sensor-based dynamometer was used for muscle strength clinical testing and it was an improved, reliable, lightweight and low-cost alternative to the conventional strain gauge systems. 136 Kim et al, produced a PDMS/CNTs strain sensor by combining it with other flexible circuits, they created a complex biomedical sensing system for stretchable applications. Additionally, they investigated the biocompatibility of the PDMS/CNTs composite and no cytotoxicity was reported, the cell viability was high and in vivo experiments proved the appropriateness of the composite for epidermal use.…”
Section: Applications Of Piezoresistive Elastomer Strain Sensors 41 Biomedical Applicationsmentioning
confidence: 99%